A psychoanalytic interpretation of bipolar disorder. (2nd April 2020) - Ventimiglia, Giancarlo
Abstract: The author proposes viewing mania as a form of defense against the state of depression resulting from "narcissistic overidentification with the depressive object" (i.e., the object in relation to which the depressive state developed), rather than as a periodic rebellion against such an internalized object. An account of the analytic psychotherapy of a clinical case of bipolar depression serves to illustrate this point of view, linked to the author's specific conception of the dynamics of depression.